PENGARUH SUPERVISI AKADEMIK TERHADAP KINERJA GURU MTs MUHAMADIYAH SUKARAME BANDAR LAMPUNG - Hadiati, Eti (Universitas Islam Negeri Raden Intan Lampung, 2018)
The research objective is to find out how much influence academic supervision has on the work performance of Muhammadiyah Sukarame Bandar Lampung Private MTs teachers. While its usefulness is expected to be useful for teachers in order to improve teacher performance related to teacher competence both pedagogical and professional competencies especially teachers of Private MTs Muhammadiyah Sukarame Bandar Lampung which can be used as a reference to improve teacher performance.